Investigating Obsolescence Issues in Mobile Phones: : An Exploratory Study - Raayan, Rafsan Rahman; Rahman, Md Mizanur (The Jahangirnagar Review, 2025)
Obsolescence is a widespread issue, with impacts on economic, social, and environmental levels. This paper aims to examine obsolescence issues in mobile phones through literature review. The different types and nature of obsolescence in mobile phones were investigated, and based on that, the influence of consumers, producers, and the practice of obsolescence itself on each other were interpreted. It has been identified that obsolescence in mobile phones occurs through disposal or hibernation, and can be attributed to absolute, functional, economic, and most importantly, psychological factors. Based on this understanding, exemplary cases were analyzed in general, with some references to the authors’ experiences in Bangladesh, and in terms of a case study into Apple's iPhones. Based on existing problems in mobile phone obsolescence, this article attempts to discover ways to combat this issue by identifying potential weak points, challenges, and resolutions, delving into discussions about topics including repair, recycling, consumerist behavior and a circular economy model. The nature of this article is largely an analytical discussion developed through the aggregation of dispersed knowledge relevant to obsolescence and its ultimate goal is to become a base upon which further research broaching into this field could be conducted.